2018
DOI: 10.3847/1538-4357/aab26f
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Magnetohydrodynamic Shallow Water Waves in the Solar Tachocline

Abstract: The influence of a toroidal magnetic field on the dynamics of shallow water waves in the solar tachocline is studied. A sub-adiabatic temperature gradient in the upper overshoot layer of the tachocline causes significant reduction of surface gravity speed, which leads to trapping of the waves near the equator and to an increase of the Rossby wave period up to the timescale of solar cycles. Dispersion relations of all equatorial magnetohydrodynamic (MHD) shallow water waves are obtained in the upper tachocline … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 50 publications
3
57
0
1
Order By: Relevance
“…For m = 1, one may get ∼ 1 yr periodicity for n = 5 or n = 6. If ǫ ≫ 1 then the period of Rossby waves increases up to the length of solar cycle (Zaqarashvili 2018). Consequently, the Rossby wave might give 1 yr periodicity in the lower part of tachocline with ǫ ≪ 1.…”
Section: Main Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For m = 1, one may get ∼ 1 yr periodicity for n = 5 or n = 6. If ǫ ≫ 1 then the period of Rossby waves increases up to the length of solar cycle (Zaqarashvili 2018). Consequently, the Rossby wave might give 1 yr periodicity in the lower part of tachocline with ǫ ≪ 1.…”
Section: Main Equationsmentioning
confidence: 99%
“…The sub-adiabatic temperature gradient leads to the significant decrease of the effective gravity in the upper part of the tachocline (Gilman 2000;Dikpati & Gilman 2005), which then causes the trapping of shallow water waves around the equator (Zaqarashvili 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Perturbations to the background state are separated using the plane wave ansatz, {u 1 , h 1 , B 1 } = {û(y),ĥ(y),B(y)}e i(kx−ωt) . The resulting ordinary differential equation, (with terms up to y 2 only 1 ) is then solved using the boundary conditions, |v| → 0 as |y| → ∞, yielding bounded solutions of the form (Zaqarashvili 2018) v n (y) = H n ( √ µy)e −(µ+d)y 2 /2 ,…”
Section: The Magnetic Modification Of Equatorial Shallow-water Wavesmentioning
confidence: 99%
“…The dashed red lines are the 95% confidence level lines for the statistical significant test. Zaqarashvili et al (2010), McIntosh et al (2015, and Zaqarashvili (2018) concluded that the solar QBO of magnetic activities should be caused by the magnetic Rossby wave instabilities. Therefore, it is an evidence that the rotational behavior of the solar corona shows the similar temporal variation as the lower atmospheric layers, and both of them might be connected with dynamical process at the base of the solar convection zone.…”
Section: Periodicity In the Plcr Time Seriesmentioning
confidence: 99%